2020
DOI: 10.3390/ani10091682
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Feed Modulates Meat Quality and Promotes the Growth of Longissimus Thoracis of Late-Finishing Pigs

Abstract: This study investigated the effect of fermented diet on growth performance, carcass traits, meat quality and growth of longissimus thoracis (LT) of finishing pigs. A total of 48 finishing pigs [Duroc × (Landrace × Large White), male, 126 ± 5-d-old] weighing 98.76 ± 1.27 kg were randomly assigned to two treatments (eight pens per treatment and three pigs per pen) for a 28-d feeding trial, including control diet and fermented diet. Fermented diet significantly increased the loin eye area and lean mass percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…In the present study, the fermented diet significantly increased carcass length and significantly decreased the average back-fat thickness. Similar results were obtained by Qiu et al (47), who reported that the fermented diet significantly increased the loin eye area and lean mass percentage of finishing pigs. However, the mechanisms underlying this observation remain unknown.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, the fermented diet significantly increased carcass length and significantly decreased the average back-fat thickness. Similar results were obtained by Qiu et al (47), who reported that the fermented diet significantly increased the loin eye area and lean mass percentage of finishing pigs. However, the mechanisms underlying this observation remain unknown.…”
Section: Discussionsupporting
confidence: 90%
“…However, the mechanisms underlying this observation remain unknown. The possible reasons of FCF to promote carcass traits may be related to increased AA profile of the feed after fermentation (47), which may play an important role in muscle accretion through increased protein synthesis signaling and suppressed degradation signaling in LDM in finishing pigs (47,48). The pH value, drip loss, CP content, and fat content are commonly used indices for evaluating meat quality of pork (34,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, compared to 0.25% group, 0.50% leucine could alleviate muscle injury and keep mitochondrial function through AMPK-TFAM pathways (Figure 5). be significantly increased the mRNA and protein levels of MyoG and MyoD [46]. In add tion, branched amino acids reduce the expression of MAFbx and MuRF1 in soleus musc by mTOR [47].…”
Section: Discussionmentioning
confidence: 91%
“…The results of this study showed that 0.50% leucine significantly increased the relative mRNA expressions levels of MyoD and MyoG, and decreased the value of MAFbx and in longissimus dorsi muscle tissue of the finishing pigs. Zhang et al ‘s experimental results on myoblast showed that leucine could be significantly increased the mRNA and protein levels of MyoG and MyoD [ 46 ]. In addition, branched amino acids reduce the expression of MAFbx and MuRF1 in soleus muscle by mTOR [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fermented products contain not only proteins, minerals, and vitamins but also living or dried cells of lactic acid bacteria or yeast, which can affect probiotically or prebiotically the digestive tract microflora [4,5]. The supplementation of the diet with fermented components has beneficial effect on the growth of pigs and regulation of the intestinal microflora because it improves the digestibility of protein and amino acids, and it reduces the concentration of antinutritional factors [3,[6][7][8][9]. Currently, soybean meal (SBM) is a basic high-protein component used in the production of complete diets for pigs.…”
Section: Introductionmentioning
confidence: 99%